EKSTRAKSI SENYAWA ANTOSIANIN DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) MENGGUNAKAN METODE MICROWAVE ASSISTED HYDRODISTILLATION (MAHD) - Qifni Yasa Ash Shiddiqi; Achmad Dwitama Karisma (Jurnal Chemurgy, 2021)
One of the problems in Indonesia is the use of synthetic dyes in textiles and food. Synthetic dyes themselves can be replaced by natural dyes that are safer for health. Natural dyes can be produced from the pericarp of red pitaya (Hylocereus polyrhizus). The pericarp of the red pitaya has an anthocyanin content of 186.90 mg/100gram. The taking of anthocyanin compounds is usually done using several types of extraction methods. This study used Microwave-Assisted Hydrodistillation (MAHD) method. This method can utilize microwaves to extract natural material compounds. Extraction is performed using ethanol-water solvent (4:1 ratio), material size of ≤0.25 mm with variations in extract time of 2, 4, and 6 minutes. This research discovered that the optimum conditions were at 4 minutes in the MAHD method with an anthocyanin concentration of 52,184 (mg / 100g).